The Arabidopsis CDK inhibitor ICK3/KRP5 is rate limiting for primary root growth and promotes growth through cell elongation and endoreduplication - Wen, Bo (Journal of experimental botany, 2013)
The coordination of plant cell division and expansion controls plant morphogenesis, development, and growth. Cyclin-dependent kinases (CDKs) are not only key regulators of cell division but also play an important role in cell differentiation. In plants, CDK activity is modulated by the binding of INHIBITOR OF CDK/KIP-RELATED PROTEIN (ICK/KRP). Previously, ICK2/KRP2 has been shown to mediate auxin responses in lateral root initiation. Here are analysed the roles of all ICK/KRP genes in root growth. Analysis of ick/krp null-mutants revealed that only ick3/krp5 was affected in primary root growth. ICK3/KRP5 is strongly expressed in the root apical meristem (RAM), with lower expression in the expansion zone. ick3/krp5 roots grow more slowly than wildtype controls, and this results not from reduction of division in the proliferative region of the RAM but rather reduced expansion as cells exit the meristem. This leads to shorter final cell lengths in different tissues of the ick3/krp5 mutant root, particularly the epidermal non-hair cells, and this reduction in cell size correlates with reduced endoreduplication. Loss of ICK3/KRP5 also leads to delayed germination and in the mature embryo ICK3/KRP5 is specifically expressed in the transition zone between root and hypocotyl. Cells in the transition zone were smaller in the ick3/krp5 mutant, despite the absence of endoreduplication in the embryo suggesting a direct effect of ICK3/KRP5 on cell growth. It is concluded that ICK3/KRP5 is a positive regulator of both cell growth and endoreduplication